Sir Thomas More - Munday, Anthony 1553-1633 (The Arden Shakespeare. Third series., 2011)
An Elizabethan play by Anthony Munday and others that depicts the life of Thomas More. It survives only in a single manuscript, now owned by the British Library. Its main claim to fame is that three pages of it may have been written by William Shakespeare's hand, but the manuscript is also important for what it reveals about censorship of Elizabethan drama.